2008
DOI: 10.1038/leu.2008.267
|View full text |Cite
|
Sign up to set email alerts
|

The key role of stem cell factor/KIT signaling in the proliferation of blast cells from Down syndrome-related leukemia

Abstract: Transient leukemia (TL) has been observed in approximately 10% of newborn infants with Down syndrome (DS). Although treatment with cytarabine is effective in high-risk TL cases, approximately 20% of severe patients still suffer early death. In this study, we demonstrate abundant KIT expression in all 13 patients with GATA1 mutations, although no significant difference in expression levels was observed between TL and acute myeloid leukemia. Stem cell factor (SCF) stimulated the proliferation of the TL cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…To directly test whether TL-blasts can fulfill this intrinsic eosinophil program during differentiation, we cultured sorted TL-blasts from three patients (for GATA1s status see Supplementary Table 1) in medium containing G-CSF, GM-CSF, IL3 and SCF (40). Under these culture conditions, normal CD34 + -hematopoietic stem and progenitor cells (HSPCs) differentiate into monocytes and granulocytes (Figure 2b and 3c–d) (41).…”
Section: Resultsmentioning
confidence: 99%
“…To directly test whether TL-blasts can fulfill this intrinsic eosinophil program during differentiation, we cultured sorted TL-blasts from three patients (for GATA1s status see Supplementary Table 1) in medium containing G-CSF, GM-CSF, IL3 and SCF (40). Under these culture conditions, normal CD34 + -hematopoietic stem and progenitor cells (HSPCs) differentiate into monocytes and granulocytes (Figure 2b and 3c–d) (41).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we tried to search mutations of TRIB1 in cases of ML-DS and TL in which such mutations are infrequent. 9 In a case of DS-AMKL (case 84), a nucleotide change from guanine to thymine has been identified at 902 that results in amino acid alteration from arginine 107 (R107) to leucine ( Figure 1B). The sequence changes were confirmed by subcloning the PCR product into the TA-type plasmid vector (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…KIT is a Sox2 enhancer-interacting gene assayed by 4C-seq (circular chromosome conformation capture) in human embryonic stem cells (28). Previous research indicated that KIT promotes proliferation and invasion by activating the PI3K-AKT pathway in some human carcinomas (29,30). For this reason, we wondered whether miR-200c participates in the growth and metastasis of CRCs through the PI3K-Akt pathway.…”
Section: Mir-200cmentioning
confidence: 99%